The Influence of Product Quality, Price, and Product Design on Purchase Satisfaction of Local Ventela Brand Shoes among Students - Siregar, Dedy Rahman; Nasution, Muhammad Irwan Padli; Atika, Atika (Universitas Islam Negeri Sumatera Utara, 2025)
An important dimension when assessing a product is its quality, namely the extent to which the product is able to perform according to its intended function. This quality describes the product's ability to meet consumer preferences. Typically, qualities that are not visible at the purchase stage will be revealed when the product is used. This study was conducted to determine how product quality, price, and design affect the satisfaction of UINSU students in purchasing Ventela shoes. A quantitative approach was applied using a questionnaire as the primary data source. The number of respondents consisted of 100 students who use Ventela shoes selected through Purposive Sampling. Multiple Linear Regression Analysis using SPSS version 16 was used to test the influence of the variables of product quality, price, and design. The results of the reliability test showed that Cronbach's alpha was between 0.730 and 0.881, so that all variables were declared reliable because they had exceeded the threshold of 0.60. The product quality variable obtained a t-count of 2.077, which was greater than the t-table of 1.98 with a significance of 0.040 t table 1.98, so that H3 is declared accepted.